2005
DOI: 10.1302/0301-620x.87b7.16061
|View full text |Cite
|
Sign up to set email alerts
|

A study of telephone screening and direct observation of surgical wound infections after discharge from hospital

Abstract: Post-discharge surveillance of surgical site infection is necessary if accurate rates of infection following surgery are to be available. We undertook a prospective study of 376 knee and hip replacements in 366 patients in order to estimate the rate of orthopaedic surgical site infection in the community. The inpatient infection was 3.1% and the post-discharge infection rate was 2.1%. We concluded that the use of telephone interviews of patients to identify the group at highest risk of having a surgical site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
(22 reference statements)
3
34
0
6
Order By: Relevance
“…Reilly et al found an incidence of in-patient infection of 3.1% and out-patient infection of 2.1% (total 5.2%) in total hip and total knee arthroplasties in Glasgow [18]. Gaine et al, in a study also from Glasgow, looked at 530 primary arthroplasties and found a deep infection rate of 1.1% within 6 weeks and superficial infection in as many as 10.5% of knees.…”
Section: Resultsmentioning
confidence: 99%
“…Reilly et al found an incidence of in-patient infection of 3.1% and out-patient infection of 2.1% (total 5.2%) in total hip and total knee arthroplasties in Glasgow [18]. Gaine et al, in a study also from Glasgow, looked at 530 primary arthroplasties and found a deep infection rate of 1.1% within 6 weeks and superficial infection in as many as 10.5% of knees.…”
Section: Resultsmentioning
confidence: 99%
“…The post hospital discharge follow-up by telephone is valid and secure, showing to be an efficient method for the diagnosis of SSI. (29) …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated acceptable use of telephone consultations in settings as wide ranging as follow-up after laparoscopic cholecystectomy 8 and identification of wound infection after elective joint replacement. 9 However, not all studies have shown positive outcomes, with the main deficiency in one study appearing to be the fact that telephone consultations became an additional service rather than a method of reducing outpatient clinic resource use. 10 Given the increasing use of telephone consultations in a variety of situations, it is perhaps surprising that relatively few studies have evaluated its use in urological situations.…”
Section: Introductionmentioning
confidence: 99%